The past in the present: race, gender and transnationalism in Zoë Wicomb's October and Chimamanda Ngozi Adichie's Americanah - Nthunya, Manosa (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
This thesis will interrogate the ways in which the most recent novels of Zoë Wicomb and Chimamanda Ngozi Adichie (namely October and Americanah) explore race, gender and transnational issues. Wicomb and Adichie share an interest in representing the lives of people who have been historically marginalised by racial and gender classifications. This thesis will argue that historical and stereotypical ways of looking at people, particularly African people, are still prevalent in the twenty-first century. Wicomb's interest is in the coloured community and the impact that apartheid ideology has had on it. She shows, as this thesis will argue, that notions of shame and respectability still influence the coloured community, post-1994, in the same ways they did under apartheid. Furthermore, the thesis will show that religion, which was used to justify apartheid, has been instrumental in maintaining racist and sexist norms in the coloured community in post-apartheid South Africa. Adichie's novel, on the other hand, shows the impact of gender norms in Nigeria on her female characters. Unlike characters in Wicomb's novel, Adichie's mostly experience racial bias when they move to Western countries. This thesis will argue that many Western countries, which were the main beneficiaries of colonialism, continue to 'other' Africans, in spite of their claims to respect all human beings. Wicomb's and Adichie's novels depict characters that are moving between different continents, along with the impact that this has on them. In the twenty-first century, more people are moving between different spaces and, as a result, interacting with different cultures. These migrations, as this thesis will show, give rise to paradoxical circumstances: people are still being judged according to their race and gender, in spite of the freedom that these moves are supposed to lead to. Of central importance to both novels then is the question of home and belonging. Since people are moving between different continents, is it still possible to belong to one place? Is it in fact possible to belong at all? These are some of the questions that will be raised and answered in this thesis. Lastly, the thesis will look at the thematic representations of reading and writing in the novels under consideration. This is most evident in Adichie's novel where her main character starts blogging as a way to express her dissatisfaction with the racist and sexist environment she encounters in the United States of America. The thesis will explore how Adichie examines blogging as a mode of communication that is unique to the twenty-first century. It will argue that it is perhaps through new media that historically subjugated subjects, such as African people and women, will be able to express themselves. Less hackneyed modes of communication might provide the necessary channels for those who have historically been denied voice to finally find it.
Keywords: Uncatalogued